If f ( x ) = ( x + 1 ) 3 ( x 2 − 1 ) 2 , what is the value of f ′ ( 2 ) ?
Details and assumptions
f ′ ( x ) denotes the derivative of f ( x ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Let y = f ( x ) = ( x + 1 ) 3 ∗ ( x 2 − 1 ) 2 Take l o g of both sides and differentiate with respect to x to get
d x d y = ( x + 1 ) 3 ∗ ( x 2 − 1 ) 2 ( x + 1 3 + x 2 − 1 4 x ) Now put x = 2 to get f ′ ( 2 ) = 8 9 1
Don't you think you've to make sure that f ( x ) attains positive real values before taking lo g on both sides ( assuming f ( x ) to be real valued ) ?
Notice that, f ( x ) > 0 ∀ x ∈ ( − 1 , 1 ) ∪ ( 1 , ∞ ) , so, in this interval \f ′ ( x ) = f ( x ) ⋅ ( x + 1 3 + x 2 − 1 4 x ) .
Note that, 2 ∈ ( − 1 , − 1 ) ∪ ( 1 , ∞ ) , hence, we can substitute x = 2 in the obtained expression of f ′ ( x ) to get f ′ ( 2 ) = 8 9 1 .
it is little bit long, but you will get 891 surely
Just expand the function: f(x)=x^7+3x^6+x^5-5x^4-5x^3+x^2+3x+1--->Now find derivative using the all mighty power rule: f'(x)7x^6+18x^5+5x^4-20x^3-15x^2+2x+3---> Substitute 2 for x (I'm skipping the cumbersome algebra as I know you all can understand). Answer is 891
Problem Loading...
Note Loading...
Set Loading...
I used chain rule on (x+1)^3 and (x^2 - 1)^2 separately. Then I applied product rule.